2015
DOI: 10.5539/jas.v7n7p156
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Effects of Increasing Levels of Pigeon Pea Meal on Rabbit Performance

Abstract: Conventional feedstuffs in Nigeria are expensive, which has led to the search for cheap and locally available unconventional feeding materials. This study was therefore conducted to determine the dietary effect of roasted pigeon pea meal (RPP) on the performance of rabbits. A total of forty weaner rabbits (20 male and 20 female) Dutch × Chinchilla rabbits with an average initial weight of 725 g and between 5 and 7 weeks old, were allocated into four dietary treatments. Each treatment had ten rabbits and five r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…By boiling 97.84% of trypsin inhibitor can be reduced in Pp seeds. Similarly, by toasting or dry heating, 89.82% of trypsin inhibitor can be reduced in the seeds (18,(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By boiling 97.84% of trypsin inhibitor can be reduced in Pp seeds. Similarly, by toasting or dry heating, 89.82% of trypsin inhibitor can be reduced in the seeds (18,(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Amaefule et al (17) reported that the chemical composition of Pp depends on cultivar, geographical location, and growth conditions. Roasted Pp can successfully be included up to 30% in the diets of rabbits without adverse effect on performance (18).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are no adverse effects on the most meat yielding components except the reduction of pre‐slaughter weight, semi‐eviscerated weight and hind leg weight as the pigeon pea leaves content increasing. Some results on pigeon pea seeds suggested boiled pigeon pea seed meal could substitute 20% maize meal and 43.9% soybean meal separately in rabbit diets; moreover, up to 30% pigeon pea seed meal could be included in the ration of rabbits and cockerels without adverse effects on growth performance and carcass traits (Akande, ; Amaefule, Ironweed, & Ojewola, ; Amaefule & Obioha, ; Yisa et al, ). However, there is no published study on pigeon pea leaves available for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…The use of alternative ingredients for animal nutrition has been of great interest to many researchers over several decades particularly, in developing countries, where conventional sources are usually more expensive (Akande, ). In Brazilian cuniculture, most of the ingredients used as part of the diets are grown solely for this purpose, occupying farm areas that could be otherwise used for growing grains for intended for human consumption and hence increasing the overall cost of the final product (Klinger et al., ).…”
Section: Introductionmentioning
confidence: 99%